36+2y=-4y

Simple and best practice solution for 36+2y=-4y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36+2y=-4y equation:


Simplifying
36 + 2y = -4y

Solving
36 + 2y = -4y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '4y' to each side of the equation.
36 + 2y + 4y = -4y + 4y

Combine like terms: 2y + 4y = 6y
36 + 6y = -4y + 4y

Combine like terms: -4y + 4y = 0
36 + 6y = 0

Add '-36' to each side of the equation.
36 + -36 + 6y = 0 + -36

Combine like terms: 36 + -36 = 0
0 + 6y = 0 + -36
6y = 0 + -36

Combine like terms: 0 + -36 = -36
6y = -36

Divide each side by '6'.
y = -6

Simplifying
y = -6

See similar equations:

| 5x+9-3x=0 | | X^2-4x-k+4=0 | | x+73=4961 | | 29-y=37 | | 5x+9=11x-27 | | (x)(4x+5)=520 | | 2y=-3x+29 | | -7x+9=19-3x | | -2y-3y+9=4-3-y | | 600=300+10c | | X^2-12x+49=22 | | 13y+2=9y+22 | | 97b=2037 | | 14x-9x=7 | | 11n^2=5n^2 | | 16b=128 | | 600=5s+400 | | x-.16x=543.90 | | 11x-4=117 | | x-.16=543.90 | | 600=175+10c | | 4n-3=4n-3 | | 4y^2+36y+72=0 | | 5/4(a-8=2/3 | | 3x[x-3]=6 | | 600=50+10c | | 7y-3y=18 | | x-0.24x=519.21 | | 2x-9+7x+13+41=180 | | y=-2(x+3)(x-4) | | x-.24x=519.21 | | 1.5y=3y |

Equations solver categories